2016
DOI: 10.1080/00016489.2016.1183817
|View full text |Cite
|
Sign up to set email alerts
|

Subjective hearing-related quality-of-life is a major factor in the decision to continue using hearing aids among older persons

Abstract: Speech discrimination score and dynamic range did not significantly differ between HA users and non-users. A difference in the average hearing threshold was marginally significant. The response rate to the HHIE was 65.2%. Total HHIE and emotional scores were higher (more impaired) among HA users than non-users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
3
14
0
2
Order By: Relevance
“…The coefficients indicated that persons who were willing to use HAs perceived a higher hearing handicap as indicated by higher HHIE/A scores. This implies that a considerable amount of perceived handicap might be required to accept the necessity of aiding; this corresponds to recent findings showing the experience of higher handicap of HA users in relation to non-users (Maeda et al 2016). Furthermore, Gopinath et al (2011) reported a regression model in which a HHIE score (screening version) of 8 and higher was a significant predictor for the incidence of HA ownership and use as dependent variables.…”
Section: Aiding Statussupporting
confidence: 79%
See 1 more Smart Citation
“…The coefficients indicated that persons who were willing to use HAs perceived a higher hearing handicap as indicated by higher HHIE/A scores. This implies that a considerable amount of perceived handicap might be required to accept the necessity of aiding; this corresponds to recent findings showing the experience of higher handicap of HA users in relation to non-users (Maeda et al 2016). Furthermore, Gopinath et al (2011) reported a regression model in which a HHIE score (screening version) of 8 and higher was a significant predictor for the incidence of HA ownership and use as dependent variables.…”
Section: Aiding Statussupporting
confidence: 79%
“…Associations between HHIE/A scores and mental-health ratings have also been described as being smaller compared to general health scores (Alpass et al 2001). In some studies, HHIE/A scores were interpreted as hearingrelated QoL (Maeda et al 2016), which might not be precise enough, since not all aspects of health-related QoL are included in the HHIE/A items (Stika and Hays 2015).…”
Section: Age Frailty and Health-related Qolmentioning
confidence: 99%
“…157 patients were included in the study who were older than 65 years. People with higher life satisfaction use their hearing aids more often and more consequently, audiological parameters, however, only have a minor impact [ 77 ].…”
Section: Necessity Of Early Hearing Rehabilitation and Hearing Aidmentioning
confidence: 99%
“…Befragt wurden 157 Patienten, die älter als 65 Jahre waren. Person mit größerer Lebenszufriedenheit tragen ihre Hörgeräte eher und konsequenter, dagegen haben audiologische Parameter kaum Einfluss [77].…”
Section: Fa Zitunclassified